Analisis Pengaruh Kreativitas Kewirausahaan terhadap Kesiapan Bekerja Siswa - Nurhikmawati; Thamrin Tahir; Muhammad Hasan (Journal of Economic Education and Entrepreneurship Studies, 2020)
The purpose of this study is to determine the effect of entrepreneurial creativity on student readiness (SMKN 1 Sinjai). This type ofresearch is quantitative research. Data obtained through the distribution of questionnaires with a Likert scale. The population in this study were all class XI and XII majors online business and marketing of SMKN 1 sinjai totaling 72. The results of this study indicate that creativity has a significant effect on the value of Sig. = 0,000 <0.05 which means it meets the significant criteria, while the T-count is 10.845> 1.666 which means it rejects null hypothesis and accept alternative hypotheses for testing both variables Based on the regression test it is known that the creativity variable has a contribution of 62.7 percent to work readiness, while based on thedescriptive test it can be concluded that work readiness of students has not been able to form optimally that there are still 16 students out of 72 students whose work readiness is still low